Jane - Goodall, Jane, 1934-; Morgen, Brett; Burk, Bryan, 1968-; Smith, James A, (Producer); Gerber, Tony; Glass, Philip; Lawick, Hugo van, 1937-; National Geographic Studios; Public Road Productions; National Geographic Documentary Films; National Geographic Society (U.S.); Twentieth Century Fox Home Entertainment, Inc. ([Washington, D.C.] : National Geographic, 2017)
Looks back at Jane Goodall's career as a primatologist, animal rights advocate, and environmental activist. Comprised of present-day interview segments with Goodall and archival footage of her work studying chimpanzees at Tanzania's Gombe National Park shot by Hugo van Lawick in the 1960s for National Geographic.
Documentary.
Includes photography by Hugo van Lawick in the National Geographic archives.
Originally released as a motion picture in 2017.
Original score, Philip Grass ; edited by Joe Beshenkovsky ; animation by Stefan Nadelman ; director of photography, Ellen Kuras.
MPAA rating: PG (parental guidance suggested; some material may not be suitable for children) for thematic elements involving animal behavior and brief smoking images.
DVD; NTSC, Region 1; widescreen presentation, 1.78:1 aspect ratio; Dolby Digital 5.1.
Keywords: Goodall, Jane, -- 1934-; Primatologists -- England -- Biography; Primatologists -- Tanzania -- Biography; Women primatologists -- England -- Biography; Women primatologists -- Tanzania -- Biography; Chimpanzees -- Tanzania -- Gombe National Park; Documentary films; Nature films; Science films; Nonfiction films; Animal films; Biographical films